Features of the concentration of vitamin and mineral compounds in women with antenatal fetal death in anamnesis at the pre-pregnancy stage. - Ilnytska, Tetiana; Beniuk, Vasyl; Hychka , Nazarii; Oleshko, Viktor; Chebotarova, Antonina (The Ukrainian Scientific Medical Youth Journal, 2025)
Antenatal fetal death is one of the most severe obstetric condition, which has a significant impact on both somatic health and the psycho-emotional state of the woman. Recently, the data appeared that highlight the role of vitamin-mineral balance in the antenatal fetal death etiopathogenesis due to the influence on the angiogenesis and on the formation of placental blood flow processes. Therefore, studying the vitamin-mineral compounds levels in women with a history of antenatal fetal death is particularly relevant and prompted the formation of our study purpose: to determine the features of the folic acid, vitamins B, D, ferritin, homocysteine concentrations in women with antenatal fetal death in anamnesis at the stage of pre-pregnancy preparation. Materials and methods of the study — a prospective examination of 82 patients was conducted, of which 49 women (main group) with antenatal fetal death in anamnesis and 33 women (control group) with no late reproductive losses in anamnesis. In all patients, the levels of folic acid, vitamins B1, B6, B12, 25-hydroxyvitamin D, ferritin, Mg2+, Se2+ and homocysteine in the blood serum were determined. The concentration of vitamins D, B₁, B₆, B₁₂, folic acid, ferritin and homocysteine was determined using enzyme-linked immunosorbent assay (Monobind (USA)). The determination of Mg2+ concentration was carried out using the colorimetric method (Roche Diagnostics, Switzerland). Selenium was determined using atomic absorption spectrophotometry (PerkinElmer, USA). According to the results obtained, the women in the main group had statistically significant differences in compared with the control group women: lower concentration of folic acid by 28.2%, vitamin B₆ by 24.3%; B₁₂ by 23.7%, Vitamin D was 18.4±1.1 ng/ml, which is 15.6% less than in the control group and 38.7% less than the lower limit of reference values. The concentration of Mg2+ was recorded as 1.4 times lower, as well as Se2+ 1.2 times in the main group. Alterations in the vitamin and mineral profile can contribute to the activation of oxidative stress, endothelial dysfunction and, as a result, placental insufficiency, which are currently considered one of the key pathogenetic links of antenatal fetal death. The obtained results emphasize the feasibility of the vitamin and mineral compounds levels determination in the pre-pregnancy preparation of women with a burdened obstetric history, which will allow the formation of individual strategies to prevent pregnancy complications and repeated perinatal losses.